Development of bicycle powered water pump - Zaihin, Mohd Zahib (2012)
Bicycle powered water pump is a water pumping system that instead of using electric powered, it will used the human power to rotate the pump so it can pumping the water. The main objective of this project is to develop the bicycle powered water pump. Basically the current water pump did not compete with a best future which is meeting the ergonomic and economic requirement. It is to fulfil the requirement base on farmers and human activity at third world countries that difficult to get the water supply and did not have electric supply. Design of bicycle powered water pump selected based on Pugh concept selection that includes concept design base on adaptation, pump selection, driving mechanism, and stand design selection. The best concept is fabricated and assembled with bicycle. The bicycle powered water pump is tested on pumping water with different water head, different gearing system, and with different human categories. From the experiment, it can conclude that 6th gear on the bicycle can produce larger flow rate with 20 I/min 0 elevation of head and on human categories, the athlete leading in producing the water flow rate from others with average 14 to 15 I/min at 0 elevations of head of 3rd gear.